New Non-Travelling Wave Solutions of Calogero Equation (Advances in Applied Mathematics and Mechanics, 2021)
In this paper, the idea of a combination of variable separation approach andthe extended homoclinic test approach is proposed to seek non-travelling wave solutionsof Calogero equation. The equation is reduced to some (1+1)-dimensionalnonlinear equations by applying the variable separation approach and solves reducedequations with the extended homoclinic test technique. Based on this idea and withthe aid of symbolic computation, some new explicit solutions can be obtained.